Experiences of injured student-athlete of the University of the Philippines Diliman on the utilization of the university's injury management services - de los Angeles, Maria Lissandra Sausa 2001-
Student-athletes undergo a multitude of challenges as they attempt to bear the load of academic and athletic responsibilities. Studies have shown that added stressors can lead to an increased risk of injury, given the multifaceted nature of sports injuries. With this understanding, the state university in Metro Manila has launched several initiatives to aid in their student-athletes' holistic development. However, as of 2023, there has been an influx of student-athletes referred to rehabilitation, suggesting increased injury incidence. This study collated the perspectives and experiences of currently and previously injured student-athletes via semi-structured interviews to determine whether they are obtaining their physical and psychological needs through the University's initiatives for injury management. The participants consisted of six (6) student-varsity athletes of the selected state university enrolled in A.Y. 2023-2024 who have spent at least one semester in their respective varsity teams and are currently injured or have been injured in the past five years. Through thematic analysis based on related literature, the study was able to 1) describe the injury management services of the selected state university; 2) describe the subsequent action(s) of the injured student-athletes who availed or did not avail these systems; and 3) analyze the experiences of the injured student-athletes regarding the injury management services of the selected state university. It was concluded that student-athletes should avail the state university’s injury management services with considerations for accommodation and comprehensive visibility on application details